(untitled) (Eurasian Medical Research Periodical, 2024)
Eleсtroson neyrotherapy is a method based on which is the impact on the Central nervous system (CNS). Patient affects constant pulse current (rectangular), low frequency and small current. This pulse current specified parameters at impact of causes the patient’s condition close to the physiological sleep. “Electroson Supromed” apparatus beneficially affects to the area of the brain and reaches sensitive nuclei of cranial nerves, pituitary, hypothalamus, reticular formation and other structures of the brain. This method is used in diseases on the basis of which is functional violations of CNS. Developed by the unit is designed to neuro-mental disease in Pediatrics, therapy, surgical practice, skin clinic, gynecology and in other cases where shown treatment unit "Electroson Supromed".